Synergy of PBA IAIM Sinjai Students in Grounding Arabic in Remote Villages - Sulfikar; Nurul Fazwani; Amran Ar (Jurnal Pengabdian Masyarakat Formosa, 2023)
The lack of attention to learning Arabic makes Arabic a language that is marginalized from people's lives. Getting around this phenomenon, PBA IAIM Sinjai students initiated an Arabic language training program as an effort to attract the attention and interest of remote communities in learning Arabic and change their perspective that Arabic is not a primitive language. The type of research used is field research using a qualitative descriptive approach by means of which the researcher is directly involved with the community regarding the program to be implemented. Methods of data collection using observation, interviews, implementation of learning programs and documentation. The data analysis technique uses Miles and Huberman's theory which includes data reduction, display or presentation of data, then conclusions. The efforts made in this study were to use an Arabic language learning model which was packaged in an attractive way so as to show the enthusiasm of the local community and foster their love for learning Arabic.